2011
DOI: 10.1002/hep.24371
|View full text |Cite
|
Sign up to set email alerts
|

Resistance mutations define specific antiviral effects for inhibitors of the hepatitis C virus p7 ion channel

Abstract: The hepatitis C virus (HCV) p7 ion channel plays a critical role during infectious virus production and represents an important new therapeutic target. Its activity is blocked by structurally distinct classes of small molecules, with sensitivity varying between isolate p7 sequences. Although this is indicative of specific protein-drug interactions, a lack of highresolution structural information has precluded the identification of inhibitor binding sites, and their modes of action remain undefined. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
106
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(118 citation statements)
references
References 50 publications
9
106
0
3
Order By: Relevance
“…p7 channels also adopt multiple conductance states and exhibit 'burst activity', with a strong influence afforded by the membrane environment, potentially via effects on the overall channel structure. p7 from a variety of genotypes has also been shown to conduct small molecules, such as the pH-sensitive fluorophore HPTS (8-hydroxypyrene-1,3,6-trisulfonic acid) (Wozniak et al, 2010) and carboxyfluorescein (StGelais et al, 2007), indicative of channel-pore dualism; one study recently questioned the relevance of such behaviour (Gan et al, 2014), yet indirect systems are widely utilized in viroporin studies, including by these same authors , and results faithfully and consistently reproduced those obtained for infectious HCV culture (Foster et al, 2011(Foster et al, , 2014Griffin et al, 2008;Wozniak et al, 2010). In this regard, the ability of p7 to mediate proton conductance within infected Huh7 cells remains the only activity for which a biologically relevant function has been assigned within the HCV life cycle (Wozniak et al, 2010), although roles for other observed conductances cannot be ruled out.…”
Section: Hcv P7mentioning
confidence: 69%
See 4 more Smart Citations
“…p7 channels also adopt multiple conductance states and exhibit 'burst activity', with a strong influence afforded by the membrane environment, potentially via effects on the overall channel structure. p7 from a variety of genotypes has also been shown to conduct small molecules, such as the pH-sensitive fluorophore HPTS (8-hydroxypyrene-1,3,6-trisulfonic acid) (Wozniak et al, 2010) and carboxyfluorescein (StGelais et al, 2007), indicative of channel-pore dualism; one study recently questioned the relevance of such behaviour (Gan et al, 2014), yet indirect systems are widely utilized in viroporin studies, including by these same authors , and results faithfully and consistently reproduced those obtained for infectious HCV culture (Foster et al, 2011(Foster et al, , 2014Griffin et al, 2008;Wozniak et al, 2010). In this regard, the ability of p7 to mediate proton conductance within infected Huh7 cells remains the only activity for which a biologically relevant function has been assigned within the HCV life cycle (Wozniak et al, 2010), although roles for other observed conductances cannot be ruled out.…”
Section: Hcv P7mentioning
confidence: 69%
“…Viable full-length HCV containing IRES elements inserted between E2 and p7 or p7 and NS2 argued against a functional role for p7 precursors (Jones et al, 2007). Both early-and late-acting defects in virion production have been described where p7 was (partially) deleted, mutated at specific residues or treated with inhibitors (Bentham et al, 2013;Foster et al, 2011Foster et al, , 2014Jones et al, 2007;Steinmann et al, 2007a;Vieyres et al, 2013;Wozniak et al, 2010). This is now known to result from p7 performing multiple functions within infected cells, comprising distinct protein-protein interactions as well as its channel-forming activity.…”
Section: Hcv P7mentioning
confidence: 99%
See 3 more Smart Citations